IMPROVING STUDENTS’ READING COMPREHENSION THROUGH MIND MAPPING TECHNIQUE OF VIII GRADE AT SMP N 5 TOLITOLI - Marzuki Marzuki (Jurnal Madako Education, 2019)
The objective of this research is to find out whether mind mapping strategy can improve students’ reading comprehension or not..This research is pre experimental research design consist of one group pre-test and post-test. The Population of this research is the eighth grade of SMPN 5 Tolitoli in 2016/2017 academic year. The sample of this research is selected by using purposive sampling technique and the selected class is VIII b consisted of 21 students. In collecting the data, the researcher took from the result of pre-test and post-test. The researcher analized the data  statically.The result of the test showed that the students’ mean score in posttest 81.14 is higher than pretest 51.4  To know the significant difference between pretest and posttest, the researcher compared the value of t-counted and t-table by applying 0.05 level of significance for two-tailed test with 20 degree of freedom (21-1=20), the researcher found that the tcounted (15,98) is higher than ttable (2,080) and the hypothesis of this research is accepted.The researcher concluded that application mind mapping strategy can improve students’ reading comprehension of eight grade at SMP N 5 Tolitoli.  Key words:improving reading comprehension,and mind mapping.